2000
DOI: 10.1097/00005537-200007000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Magnetic Stimulation in Acute Facial Nerve Injury

Abstract: Objective/Hypothesis Available electrodiagnostic tests that are used to evaluate facial nerve injury examine the nerve distal to the stylomastoid foramen; because most facial nerve injuries are within the temporal bone, the tests cannot evaluate the nerve at or across the injury site. The interpretation of these tests depends on the predictability (or unpredictability) of distal degenerative process. Transcranial magnetic stimulation may be able to stimulate the nerve proximal to the injury site. The hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…Different from the mechanism of peripheral TMS stimulation, the effective mechanism of central TMS stimulation may be the use of high-frequency (excitatory) TMS elicitation to guide the activation of the brain cortex representative area of facial movement, which is helpful to the remodeling of the facial muscle motor function, and the nerve impulse excited will also project to the facial nervous system, to accelerate the recovery of facial nerve function (31). There have been multiple studies showing that in patients with peripheral facial paralysis, the representative area of the cerebral cortex related to facial muscle decreases (32), the adjacent area (such as the forearm muscle cortex representative area) increases, and the functional remodeling of facial motor cerebral cortex representative area is closely related to the prognosis of patients with peripheral facial paralysis (20,33,34). Functional magnetic resonance imaging (fMRI) studies by Hu et al suggested that cortical reorganization plays an important role in the recovery of Bell's facial paralysis (35).…”
Section: Discussionmentioning
confidence: 99%
“…Different from the mechanism of peripheral TMS stimulation, the effective mechanism of central TMS stimulation may be the use of high-frequency (excitatory) TMS elicitation to guide the activation of the brain cortex representative area of facial movement, which is helpful to the remodeling of the facial muscle motor function, and the nerve impulse excited will also project to the facial nervous system, to accelerate the recovery of facial nerve function (31). There have been multiple studies showing that in patients with peripheral facial paralysis, the representative area of the cerebral cortex related to facial muscle decreases (32), the adjacent area (such as the forearm muscle cortex representative area) increases, and the functional remodeling of facial motor cerebral cortex representative area is closely related to the prognosis of patients with peripheral facial paralysis (20,33,34). Functional magnetic resonance imaging (fMRI) studies by Hu et al suggested that cortical reorganization plays an important role in the recovery of Bell's facial paralysis (35).…”
Section: Discussionmentioning
confidence: 99%